Insulinomimetic Effect of Citrullus Colocynthis Roots in STZ Challenged Rat Model: Insulinomimetic Effect of Citrullus Colocynthis Roots - Kalva, Sireesha; Fatima, Nishat; .N, Raghunandan; Samreen, Saba (Iranian Journal of Pharmaceutical Sciences, 2018)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia resulting from either defect in insulin secretion, insulin action, or both. Postprandial hyperglycemia is a prime characteristic of diabetes mellitus and has been a focus in the therapy for diabetes. One of the therapeutic approaches which involve decreasing hyperglycemia aims at lowering blood glucose by decreasing insulin resistance, raising insulin sensitivity at the tissues and inhibiting the carbohydrate absorbance in the intestine. Plants contain different chemical constituents with potential for insulin mimetic action, decrease in insulin resistance and of α-amylase inhibitory activity may be used as therapeutic agents in the treatment of diabetes mellitus. The present study investigates the hypoglycemic activity and insulinomimetic action of aqueous and ethanolic extracts of Citrullus colocynthis by invitro α-amylase enzyme inhibition and by histopathological studies in streptozotocin (STZ) induced diabetic rats. Male Wistar rats weighing about 180- 250g were taken and divided into fifteen groups. Diabetes was induced by giving streptozotocin (STZ) (30-50mg/kg) intraperitoneally. Rats that showed blood glucose levels > 250mg/dl were selected for the study. Metformin (45mg/kg) was given as standard oral hypoglycemic agent. The aqueous and ethanolic extracts of Citrullus colocynthis (AECC and EECC) at 100mg/kg, 200mg/kg and 300mg/kg were administered to the normal and diabetic rats. The invitro α – amylase inhibitory activity was done by spectrophotometric method. Blood glucose levels were measured by glucose oxidase method. Estimation of glycogen in the lever was carried out with anthrone method. Liver and pancreas were isolated and subjected to histopathological studies. Serum insulin was monitored through chemiluminescence assay. Oral administration of both extracts showed significant inhibition of α-amylase enzyme in-vitro and decrease in blood glucose also. Glycogen and Insulin levels too were found to increase in extract treated groups which attributed for its insulinomimetic activity. The findings revealed that Citrullus colocynthis possess a very strong anti-hyperglycemic potential justifying the use of the drug for the treatment of diabetes mellitus.